If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9 = -7 + 3 Reorder the terms: -9 + 4x = -7 + 3 Combine like terms: -7 + 3 = -4 -9 + 4x = -4 Solving -9 + 4x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4x = -4 + 9 Combine like terms: -9 + 9 = 0 0 + 4x = -4 + 9 4x = -4 + 9 Combine like terms: -4 + 9 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25
| 6x+4-4=180 | | (w+15)+w+45=180 | | 4x+27=x-19 | | 2(x+8)+3(7+1)=5 | | 2+1=x-9 | | 12(v+4)-3v=3(3v+1)-5 | | 8-6-2x-6=-2x-4 | | 6m-8m-3=9 | | -30=3n+-12 | | 54+c=66 | | 8-(-2x-4)=-52 | | -3+15y+17=2(5y+6) | | -7(X+7)=-5(4X+6)-6X | | 8+x+2x=90 | | 4x+17y=100 | | 8y-9=4 | | 4(3d-2)-2d=6d-6 | | 2/7(x-9)-4 | | 45=5/24x | | 5d+4d+d=180 | | -2(8X+4)+6=2(X+8) | | -20+6= | | 5x+4(-3-x)=4(x+3) | | 4x+8-9=3 | | 6.2x-1.1=11.3 | | -6y-9=3y+9 | | (x-3)(2x-1)=0 | | y+2y=90 | | 2y-38+3+3y=-105+7 | | 2/3x-4=5/4 | | 2(7-3(-3x-7))=18x+56 | | 4r(r-1)=19 |